“Câncer de pele: conhecer para melhor combater”: livro educativo em prevenção e detecção precoce do câncer de pele - Oliveira, Daniel Arcuschin de [UNIFESP] (2019)
Introduction: Among malignant neoplasms, skin cancer has the highest incidence, both in Brazil and in the world. The major skin cancers are melanomas and non-melanomas, also known as basal cell (CBC) and squamous cell carcinomas (SCC). Primary prevention and early detection are the main ways to decrease morbidity and mortality. The easy access of digital content on the internet allows the dissemination of scientific information, in accessible language, according to the target audience. The population becomes an agent of their own health, and is encouraged to seek medical attention in case of doubt. In this way, the idea of the educational book “Cancer of the skin: to know to better fight” appears in the printed and digital form (e-book). Objective: To write a book for lay people with information on prevention and early detection of skin cancer. Method: Planning and elaboration of the book “Cancer of the skin: to know to better fight” through the application of concepts of Design Thinking covering its four distinct phases: Discover, Define, Develop and Deliver. Results: The developed book has eight chapters with the following themes: "The skin", "The sun", "Moles and other signs that are not cancer", "Skin cancers", "Prevention "," Treatment "," Reconstruction "and" Glossary ". Conclusion: A book on the prevention and early detection of skin cancer was developed for the print and digital formats (e-book).